1997
DOI: 10.1126/science.277.5328.925
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between the ENSO and the Asian Monsoon in a Coral Record of Tropical Climate

Abstract: The oxygen isotopic composition of a banded coral from the western equatorial Indian Ocean provides a 150-year-long history of the relation between the El Niiio-Southern Oscillation (ENSO) phenomenon and the Asian monsoon. Interannual cycles in the coral time series were found to correlate with Pacific coral and instrumental climate records, suggesting a consistent linkage across ocean basins, despite the changing frequency and amplitude of the ENSO. However, decadal variability that is characteristic of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
205
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(214 citation statements)
references
References 18 publications
8
205
1
Order By: Relevance
“…However, the presence of such climate signals in the Beijing temperature record clearly indicates the impacts of ocean-atmosphere interactions in modulating the decadal variability of summer temperature in the mid-latitudes. This interpretation is supported by modern observations [32][33][34][35][36], consistently showing the influences of tropical SST on the East Asian monsoon climate.…”
Section: Resultssupporting
confidence: 74%
“…However, the presence of such climate signals in the Beijing temperature record clearly indicates the impacts of ocean-atmosphere interactions in modulating the decadal variability of summer temperature in the mid-latitudes. This interpretation is supported by modern observations [32][33][34][35][36], consistently showing the influences of tropical SST on the East Asian monsoon climate.…”
Section: Resultssupporting
confidence: 74%
“…[16] In the Indian Ocean, the effect of ENSO to SST and precipitation has been discussed [Reason et al, 2000], and found in coral band analysis [Charles et al, 1997;Cole et al, 2000]. While independent influence of IOD is recently discussed .…”
Section: Coral Iod Indexmentioning
confidence: 99%
“…[2] Variability in the tropical and subtropical climate in the Pacific and Indian oceans has often been explained by the variability in the El Niño Southern Oscillation (ENSO) [Charles et al, 1997;Cole et al, 2000]. However, correlation between ENSO and climate variability in the Indian Ocean is not always high [Zinke et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corals precisely record the depletion in δ 18 O sea water during the NE monsoon season by showing negative δ 18 O anomalies ( figure 3). There is a high correlation between mean December-March coral δ 18 O, precipitation and outgoing long-wave (Reynolds & Smith 1994) between 1982(Charles et al . 1997).…”
Section: (B) Chagosmentioning
confidence: 99%